Material heritage of the pastoral culture of the Western Beskids – the state of identification and documentation for the preservation of the economic and cultural identity of the region - Łach, Janusz; Helt, Marta (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The chapter concerns the problem of identification, documentation and preservation of the Wallachian cultural heritage related to the sheep-farming economy in the area of the Western Beskids. The analyzes are conducted in the context of landscape studies on the problematic border between subecumene and ecumene. The natural and cultural conditions of the Wallachian genesis shaped the shepherd-agricultural type of the seasonal mountain economy, referred to as sheep-farming. Its material goods, to a great extent of a relict nature, are described as the great ethnographic peculiarity of the region with a long and rich material heritage. Currently, this economy in the region of the Western Beskids has been abandoned and its legacy is being forgotten, therefore it seems to be an important goal to document and consolidate the type of activities leading to the preservation of regional and national identity.